Potential correlations of dentogenic factors to the development of clinically verified fungus balls: A retrospective computed tomography–based analysis. (21st July 2015) - Tomazic, Peter Valentin; Dostal, Eva; Magyar, Marton; Lang‐Loidolt, Doris; Wolf, Axel; Koele, Wolfgang; Truschnegg, Astrid; Stammberger, Heinz; Payer, Michael
Abstract : Objectives/Hypothesis: Fungus balls are a common disease of the paranasal sinuses, usually involving the maxillary sinus. To clarify the pathology, we analyzed patients treated for maxillary sinus fungus balls to see whether the latter correlated with dentogenic factors. Study Design: Retrospective case analysis. Methods: Cases of maxillary sinus fungus balls diagnosed between January 2000 and December 2013 were analyzed retrospectively. Patients' charts were reviewed for diagnosis, gender, and age. Paranasal sinus computed tomography (CT) scans were reviewed according to the side of the fungus ball, calcifications/opacifications, and dentogenic factors. Results: In 98/102 patients (96.1%), 157 dentogenic factors could be identified on the side affected by a fungus ball. On the contralateral healthy side, there were 125 dentogenic factors. In four (3.9%) of the patients, no dentogenic pathology was identified on the CT scan. The presence of dentogenic factors (regardless of number) was significantly associated with a fungus ball compared to the healthy side ( P  = .024, χ 2 test, odds ratio: 2.72 [95% confidence interval: 1.02–7.23]). Conclusions: Dentogenic factors regardless of type potentially correlate with the presence of maxillary sinus fungus ball. Unlike the overall presence of dentogenic factors, the particular dentogenic factors in an individual patient do not significantly influence the development of fungus balls. After diagnosis of dentogenic pathology in penetrated maxillary sinus floors, patients should be closely monitored and informed about their higher risk of developing a fungus ball. Level of Evidence: 4. Laryngoscope, 126:39–43, 2016